ANALISIS ARUS STARTING MOTOR 22KW DENGAN METODE SOFT STARTER DI PT. UNILEVER OLEOCHEMICHAL INDONESIA: ANALYSIS OF 22KW MOTOR STARTING CURRENT USING THE SOFT STARTER METHOD AT PT. UNILEVER OLEOCHEMICHAL INDONESIA - Habibie, Tedy Haryanto; Saputro, Ngairan Banu; Tampubolon, Darwis (Jurnal Ilmiah Tenaga Listrik, 2023)
ABSTRACT For a company or factory, especially Oleochemichal, the use of three-phase induction motors is widely used to drive equipment such as pumps. Three-phase induction motor with direct on-line system that has a high starting current with a very short starting time so it is not effective when used in electric motors above 20kW. One way to adjust the starting current of the motor is to use the Soft starter method. The use of Soft starter can be used to adjust the starting current so that when the motor is started the current will gradually rise to its nominal current in a predetermined time according to the parameter settings on the Soft starter. In the process of starting a three-phase induction motor using a soft starter, the starting voltage is used to regulate the starting current. From the results of this analysis, when given a starting voltage of 100%, the nominal current according to the measurement is 20.4A and the nominal current according to the calculation is 23.9A. Keywords: Soft starter, Starting current, three phase induction motor ABSTRAK Bagi sebuah perusahaan atau pabrik terutama Oleochemichal, penggunaan motor induksi tiga fasa banyak digunakan sebagai penggerak peralatan-peralatan seperti pompa. Motor induksi tiga fasa dengan sistem direct on-line yang memiliki arus starting yang tinggi dengan waktu starting yang sangat singkat sehingga tidak efektif apabila digunakan pada motor listrik diatas 20kW. Salah satu cara untuk mengatur arus starting pada motor adalah dengan menggunakan metode Soft starter. Penggunaan Soft starter dapat dimanfaatkan untuk mengatur arus starting sehingga ketika motor distart arus akan bertahap naik sampai ke arus nominalnya dalam waktu yang telah ditentukan sesuai dengan setting parameter pada Soft starter. Dalam proses starting motor induksi tiga fasa menggunakan Soft starter maka dimanfaatkan tegangan starting untuk mengatur arus starting. Dari hasil analisis ini apabila diberi tegangan starting sebesar 100% maka arus nominalnya sesuai pengukuran adalah 37,4A dan Arus nominal yang sesuai perhitungan adalah 37,84A Kata Kunci: Soft starter, Arus Starting, Motor Induksi tiga fasa